Characterization of human dermal fibroblasts in 3D fibrous scaffolds - Guo, Ziqi (2016)
Fibrous scaffolds replicating the extracellular matrix (ECM) have been widely researched to help regenerate soft tissues, thus become a promising alternative to cure chronic wounds. Electrospinning is an efficient method to produce such scaffolds, but the drawback is that the conventional electrospun fibers has small pore size and restrained thickness, which restricts cell growth and penetration. The commonly formed nano fibrous scaffolds are densely packed 2D structure. To solve this problem, wet electrospinning system was developed to fabricate 3D fibrous scaffold. The purpose of this research is to optimize the parameters of fabricating the 3D fibrous scaffold through wet-electrospinning, including screening of the materials (e.g. PLGA8020 and PLCL7015) and the processing parameters (e.g. voltage and feed rate). The second purpose is to characterize the morphology by SEM and the mechanical properties of PLGA8020 3D scaffolds via Instron mechanical tester. The third purpose is to characterize cellular behaviors, including proliferation, infiltration and morphology. The results showed that the optimized PLGA8020 3D fibrous scaffolds possessing pores of 5 to 25μm and defect-free fiber of 1.6 to 2.6μm. The mechanical strength is weaker than human skin. As for cell work, HDF kept growing inside the scaffold and the proliferation number increased through the 7 days’ experiment. The infiltration results showed that cells kept penetrating down the scaffold. The confocal microscopy images showed the morphology of cell adhesion on fibers, indicating the survivability of HDF. In summary, the optimized PLGA8020 3D scaffold is a promising biomaterial for chronic wound healing application.